India ASEAN bilateral relations- Emerging trends, Challenges and Opportunities - Handique, Chumki (The journal of contemporary issues in business and government, 2021)
India’s bilateral relation with ASEAN has been growing ever since they entered into partnership. Based on the secondary data, the present study tries to put forward a comprehensive analysis of the emerging India-ASEAN trade and investment relations in the last few years. The paper further analyses the key challenges to this trade relation with special reference to the challenge posed by the Covid-19 pandemic. We have also discussed how India and ASEAN have mutually engaged with each other to fight back the pandemic to their best capacities. We also highlight the emerging opportunities for India and ASEAN. Ideas and perspectives are thus, explored in the present study in order to search for a collective solution to strengthen the economic ties between India and ASEAN in the face of the changing world order due to the Covid-19 pandemic.